Videokonsultationen durch Psychotherapeuten in der Hausarztpraxis: Therapiekonzept und Ergebnisse einer Studie zur Umsetzungsbereitschaft bei Psychotherapeuten = Psychotherapeutic video consultations in primary care : concept of the PROVIDE intervention and results on the intent to adopt in psychotherapists - Haun, Markus W.; Tönnies, Justus; Oeljeklaus, Lydia; Hoffmann, Mariell; Wensing, Michel; Szecsenyi, Joachim; Friederich, Hans-Christoph; Hartmann, Mechthild (Psychotherapie, Psychosomatik, medizinische Psychologie, 2019)
Mental health conditions represent a significant burden to the individual as well as the society. Within the health care system, the general practitioner is the first and, in most cases, the only provider. Timely referral of patients to specialized care is often difficult due to several barriers, particularly in rural areas. These barriers comprise long waiting times, the rising prevalence of psychosomatic and somatopsychic comorbidity, immobility in the elderly and stigmatisation related to mental health conditions. Following the Integrated Health Care approach, diagnosis and therapy of mental health conditions by psychotherapists directly within the general practice constitute an effective care model. We present a care model that is based on a telemental treatment approach for depression and anxiety disorders. Central is the piloting of psychotherapeutic video consultations in the general practice. The following article provides an overview of the care model and provides results concerning the intent to adopt the model in office-based psychotherapists.